Forest Governance in India with Particular Reference to Andhra Pradesh: A Review of Policy Shift from State Control to Community Participation. - Bandi, Madhusudan (2011)
This paper looks into the evolution of forest governance in India with particular reference to the state of Andhra Pradesh since forests received special mention for its administration, much before the emergence of the modern forest department under the colonial regime in India. The main concern of the paper revolves round a policy shift in forest management from state control to community participation. Through a critical review of literature, the paper traces the practice of ‗participatory‘ forest management in India and Andhra Pradesh. It also illustrates how the modern concept of ‗community‘ forest management has finally come into implementation in the management of forests in Andhra Pradesh.